2020
DOI: 10.3389/fmech.2020.00020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Modeling Approaches for MILD Combustion Systems With Internal Recirculation

Abstract: Numerical simulations employing two different modeling approaches are performed and validated against experimental results from a moderate or intense low-oxygen dilution (MILD) system with internal recirculation. The flamelet-generated manifold (FGM) and partially stirred reactor (PaSR) closures are employed in a Reynolds-averaged Navier-Stokes (RANS) framework to carry out the numerical simulations. The results show that the FGM model strongly overpredicts temperature profiles in the reactive region, while yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It was used to study different coal flames (Tufano et al 2018;Wan et al 2019;Rieth et al 2019;, assess the stabilization mechanism of supersonic lifted flames (Bouheraoua et al 2017) and lifted hydrogen flames (Benim et al 2019), classify regions of industrial burners by the combustion regime , study auto-ignition of supercritical hydrothermal flames (Song et al 2019), analyze extinction and re-ignition events (Sripakagorn et al 2004) and gain insight into partially premixed DME flames . It was further applied to scram jets (Shen et al 2020;, Moderate or Intense Low oxygen Dilution (MILD) combustion (Amaduzzi et al 2020), compression ignition engines (An et al 2018), double-cone burners , coaxial diffusion flames , edge flames (Duboc et al 2019) and jet-in-hot-coflow flames in conjunction with tangential stretching rate analysis (Li et al 2019). In order to evaluate the flame index experimentally, Rosenberg et al (2013Rosenberg et al ( , 2015 introduced tracer gases.…”
Section: Introductionmentioning
confidence: 99%
“…It was used to study different coal flames (Tufano et al 2018;Wan et al 2019;Rieth et al 2019;, assess the stabilization mechanism of supersonic lifted flames (Bouheraoua et al 2017) and lifted hydrogen flames (Benim et al 2019), classify regions of industrial burners by the combustion regime , study auto-ignition of supercritical hydrothermal flames (Song et al 2019), analyze extinction and re-ignition events (Sripakagorn et al 2004) and gain insight into partially premixed DME flames . It was further applied to scram jets (Shen et al 2020;, Moderate or Intense Low oxygen Dilution (MILD) combustion (Amaduzzi et al 2020), compression ignition engines (An et al 2018), double-cone burners , coaxial diffusion flames , edge flames (Duboc et al 2019) and jet-in-hot-coflow flames in conjunction with tangential stretching rate analysis (Li et al 2019). In order to evaluate the flame index experimentally, Rosenberg et al (2013Rosenberg et al ( , 2015 introduced tracer gases.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, τ c is obtained from the ratio between the mass fraction and the formation rate of representative species, while τ m can be estimated with a static or dynamic approach. Although the dynamic method is conceptually more accurate, previous studies demonstrated very small differences in the predictions of the two methods. , For this reason, in this work, the static method was applied, also to save computational time, which expresses the mixing time as τ mix = C mix k /ε, where C mix is a mixing constant typically set to the value of 0.5, but more in general, it can vary in the range of 0.1–1. Indeed, higher or lower C mix values are representative of less or more intense mixing conditions, respectively; these directly influence the mixing time scale and, thus, the mean reaction rate.…”
Section: Numerical Modelmentioning
confidence: 99%
“…In addition, the high characteristic reaction times make MILD combustion related to low Da (<1). This requires the review of assumptions and models used for reactive fluid-dynamic modeling of these processes. ,, …”
Section: Mild Combustion: Features and Potentialsmentioning
confidence: 99%
“…This requires the review of assumptions and models used for reactive fluid-dynamic modeling of these processes. 26,56,57 The numerical modeling of such a regime must carefully consider the turbulence/chemistry interaction, and detailed kinetic mechanisms must be used. The adoption of primitivevariable-based methods (such as tabulated chemistry approaches) or reactor-based models (EDC or PaSR) were reported in the literature as the optimal ones to treat the previous issues related to MILD reactive structure modeling.…”
Section: Mild Combustion: Features and Potentialsmentioning
confidence: 99%